(3eLehY aj GdcjejGAs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hEPG bO JbOe dfG UOQ ef GdTQM ajeG JVefGg eeG JMJGL Edjg CfG bO YdefGc ai GdcJGH GdChd ef cJGHfG gPG cja hLg JYdje GdejRGf s
(3BNQgG (B:s
(3hHGddg GdJhajb aEf bGdhG EfgeG eNJdaGJ GdWHGFY Je GdLRA GdKGfi ef cJGH GdcGed s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdMGOi YTQs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B103s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdcjejGA h GdWHjYjGJs